Antibacterial activities of the extracts, fractions and compounds from Dioscorea bulbifera - Kuete Victor; BetrandTeponno Rémy; Mbaveng Armelle; Tapondjou Léon; Meyer Jacobus J; Barboni Luciano; Lall Namrita (BMC, 2012)
Abstract Background Dioscorea bulbifera is an African medicinal plant used to treat microbial infections. In the present study, the methanol extract, fractions (DBB1 and DBB2) and six compounds isolated from the bulbils of D. bulbifera, namely bafoudiosbulbins A (1), B (2), C (3), F (4), G (5) and 2,7-dihydroxy-4-methoxyphenanthrene (6), were tested for their antimicrobial activities against Mycobacteria and Gram-negative bacteria involving multidrug resistant (MDR) phenotypes expressing active efflux pumps. Methods The microplate alamar blue assay (MABA) and the broth microdilution methods were used to determine the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of the above samples. Results The results of the MIC determinations indicated that when tested alone, the crude extract, fractions DBB1 and DBB2 as well as compounds 2 to 5 were able to prevent the growth of all the fifteen studied microorganisms, within the concentration range of 8 to 256 μg/mL. The lowest MIC value for the methanol extract and fractions (16 μg/mL) was obtained with DBB1 and DBB2 on E, coli AG100A and DBB2 on Mycobacterium tuberculosis MTCS2. The lowest value for individual compounds (8 μg/mL) was recorded with compound 3 on M. smegmatis and M. tuberculosis ATCC and MTCS2 strains respectively. The activity of the samples on many MDR bacteria such as Enterobacter aerogenes EA289, CM64, Klebsiella pneumoniae KP63 and Pseudomonas aeruginosa PA124 was better than that of chloramphenicol. When tested in the presence of the efflux pump inhibitor against MDR Gram-negative bacteria, the activity of most of the samples increased. MBC values not greater than 512 μg/mL were recorded on all studied microorganisms with fraction DBB2 and compounds 2 to 5. Conclusions The overall results of the present investigation provided evidence that the crude extract D. bulbifera as well as some of the compounds and mostly compounds 3 could be considered as potential antimicrobial drugs to fight against MDR bacteria.